HISTORY OF LOCAL GOVERNMENT FROM SUBCONTINENT TO MUSHARRAF ERA - Tasneem Sarwat; Muhammad Sohaib; Shaista gohar (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
In modern days democracy has been considered as the best form of government. In this form the power remain in the hands of people. The beauty of this system is that it include all the people from top to bottom in power sharing.The local government is the lowest unit of democracy which transfer the power to the locals. These local representative work for the welfare and betterment of the people. This paper will help us to understand the concept of local government and also the evolution process in the subcontinent.